A odisséia de si: reconstrução do homem em Clarice Lispector - Fonseca, Ailton Siqueira de Sousa (2007)
Clarice Lispector s works unveil a complex Weltanschauung, both in relation to the cosmos and man s condition. Her literature is a bold and introspective plunging into the mysteries of being. In her plots things are always in the making. Her narratives are erratic as though the characters were searching the origin or the starting point of things. In this search, Lispector is faced with the unaccountable and mysterious beauty of being, with the complex human condition, which is beyond rationalization and regulating norms. The present thesis is an open reflection, an invitation to a dialogue on the human condition in Clarice Lispector s works. It stems from the novel A Maçã no Escuro, where, we believe, it is possible to notice man start his very own odyssey. Martim, the protagonist, is the man through whom it will be possible to journey through Lispector s work as a whole and to build a dialogue with other characters engendered by her. Martim is an archetypical character. This novel is here considered as a core-novel, where the subject experiences the anthropological problem of remaking himself from his roots, of becoming what he is. Therefore, this thesis has been organized around Martim s experiences, presented both in a continuous and in a discontinuous way